2014
DOI: 10.1016/j.annepidem.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Selection bias modeling using observed data augmented with imputed record-level probabilities

Abstract: PURPOSE Selection bias is a form of systematic error that can be severe in compromised study designs such as case-control studies with inappropriate selection mechanisms or follow-up studies that suffer from extensive attrition. External adjustment for selection bias is commonly undertaken when such bias is suspected, but the methods used can be overly simplistic, if not unrealistic, and fail to allow for simultaneous adjustment of associations of the exposure and covariates with the outcome, when of interest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…This study provides new evidence that elevated OPA in terms of relative aerobic workload (%VO 2 max or %VO 2 Res) predicts increased CHD and all‐cause mortality in middle‐aged working men, even at levels of relative aerobic workload that are below the recommended maximum. The findings further support the notion that inconsistencies in the literature on the cardiovascular health effects of OPA may be due to alternative choices of analytic strategies, exposure misclassification, health‐based selection bias or healthy worker effect, uncontrolled confounding, and complex interactions between cardiovascular health status, cardiorespiratory fitness, and physical job demands. Worksite primary prevention of CVD and premature death requires approaches that take the individual worker CVD health status, aerobic capacity, and the energy demands of the job into account.…”
Section: Discussionsupporting
confidence: 70%
“…This study provides new evidence that elevated OPA in terms of relative aerobic workload (%VO 2 max or %VO 2 Res) predicts increased CHD and all‐cause mortality in middle‐aged working men, even at levels of relative aerobic workload that are below the recommended maximum. The findings further support the notion that inconsistencies in the literature on the cardiovascular health effects of OPA may be due to alternative choices of analytic strategies, exposure misclassification, health‐based selection bias or healthy worker effect, uncontrolled confounding, and complex interactions between cardiovascular health status, cardiorespiratory fitness, and physical job demands. Worksite primary prevention of CVD and premature death requires approaches that take the individual worker CVD health status, aerobic capacity, and the energy demands of the job into account.…”
Section: Discussionsupporting
confidence: 70%
“…The trajectories from the selected best fitting model were compared in terms of the type of gambling activities, the frequency of gambling, and gambling problems. Moreover, the association between trajectories and problem gambling at age 30 [52][53] was applied to the GLIMMIX procedure examining the association between trajectories and gambling problems at age 30.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, adjustment or matching on important factors potentially associated with both weight change and imprisonment could be done, as was done by Baldwin et al (24), who found that weekly weight gain in their prison population was higher than race and age-matched gain in the general population. Nonetheless, future studies should be subjected to rigorous design and analysis to minimize and assess sensitivity to bias due to unmeasured confounders, measurement error and selective nonresponse (65)(66)(67)(68). The presence of publication bias suggests that many published studies focusing on weight change in prison tend to show a weight gain rather than a normal distribution of weight changes during incarceration.…”
Section: Recommendationsmentioning
confidence: 99%